2015
DOI: 10.1109/tii.2015.2479583
|View full text |Cite
|
Sign up to set email alerts
|

A New Protection Scheme Considering Fault Ride Through Requirements for Transmission Level Interconnected Wind Parks

Abstract: New grid codes impose fault ride through (FRT) requirements on large doubly-fed induction generator (DFIG) based wind parks connected to transmission systems in order to reduce the loss of huge generation power due to temporary faults. Recently, the focus is set towards the development of different wind turbine technologies to enhance the FRT capability of wind parks with no consideration for transmission system protection schemes. This paper proposes a new communication-based dual time-current-voltage trippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 21 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Moreover all of these network topologies lead to the complexity of the problem, as well as result in mis-coordination of DOCRs, constantly leading to contingencies. To overcome this issue and reduce the power outages it has been highly recommended for the relay settings to be determined optimally considering only the main system configuration [23][24][25][26]. In [27], the coordination of DOCRs was determined by a linear method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover all of these network topologies lead to the complexity of the problem, as well as result in mis-coordination of DOCRs, constantly leading to contingencies. To overcome this issue and reduce the power outages it has been highly recommended for the relay settings to be determined optimally considering only the main system configuration [23][24][25][26]. In [27], the coordination of DOCRs was determined by a linear method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, today, the voltage value can also be used to diagnose the faulty part of the power system due to the fact that directional overcurrent relays (DOCRs) have generally become more accessible and are able to measure both current and voltage values on the line which they are connected to via current and voltage transformers. The previous research showed that this feature of the DOCRs creates an opportunity for the application of N-SCs which are formed not only by taking into account the current but also the voltage value [48,49,50,10]. Some researchers have suggested to make use of voltage measurements by adding a voltage parameter to the SCs in order to mitigate the effects caused by DG connection, MG concept, etc., while others have suggested to use admittance based characteristics provided that the inverse time characteristic is preserved.…”
Section: Non-standard Characteristics Including Electrical Magnitudesmentioning
confidence: 99%
“…Improvement of protection coordination quality was provided using a non-standard characteristic in this study; however, the effect of DG connection was not considered. Using a function of voltage value along with the IEC standard characteristic, a non-standard characteristic was devised in [12,13]. Although the integration of DG was comprehensively addressed in this study, the primary operation time of the relay depended on the coordination since the relays were operated using one characteristic.…”
Section: Relevant Literaturementioning
confidence: 99%